2007
DOI: 10.1002/ajpa.20604
|View full text |Cite
|
Sign up to set email alerts
|

Niger‐Congo speaking populations and the formation of the Brazilian gene pool: mtDNA and Y‐chromosome data

Abstract: We analyzed sequence variation in the mitochondrial DNA (mtDNA) hypervariable segment I (HVS-I) from 201 Black individuals from two Brazilian cities (Rio de Janeiro and Porto Alegre), and compared these data with published information from 21 African populations. A subset of 187 males of the sample was also characterized for 30 Y-chromosome biallelic polymorphisms, and the data were compared with those from 48 African populations. The mtDNA data indicated that respectively 69% and 82% of the matrilineages foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 52 publications
9
47
0
2
Order By: Relevance
“…The results, as expected, showed a mirror image of those previously found in white Brazilians: on the one hand, 85% of the lineages originated in Sub-Saharan Africa, 12% were from Amerindians and only 3% were from Europe; on the other, only 48% of the Y chromosome lineages originated from Sub-Saharan Africa (the vast majority belonging to haplogroups E3a7 and E3a*). Studies on black individuals from the cities of Rio de Janeiro and Porto Alegre (14) produced very similar results.…”
Section: Uniparental Genetic Markers In Braziliansmentioning
confidence: 59%
“…The results, as expected, showed a mirror image of those previously found in white Brazilians: on the one hand, 85% of the lineages originated in Sub-Saharan Africa, 12% were from Amerindians and only 3% were from Europe; on the other, only 48% of the Y chromosome lineages originated from Sub-Saharan Africa (the vast majority belonging to haplogroups E3a7 and E3a*). Studies on black individuals from the cities of Rio de Janeiro and Porto Alegre (14) produced very similar results.…”
Section: Uniparental Genetic Markers In Braziliansmentioning
confidence: 59%
“…For comparative purposes, a large number of published African and Eurasian mtDNA HVS I sequences and any available HVS II or RFLP data were used (see references 1,18,19,22,23 ). In addition, complete or nearly complete mtDNA sequences pooled in MitoMap mtDNA tree 24 were taken into analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a publication of the São Paulo Research Foundation (FAPESP) devoted to disseminating the results of scientific research to the public, a report on the work of Brazilian geneticists Sérgio D. J. Pena (e.g., Pena et al 2000) and Maria Cátira Bortolini (e.g., Hünemeier et al 2007) said the geneticists' research showed that "the first groups of European colonists . .…”
Section: Popular Science: Mothers and Fathersmentioning
confidence: 99%